Inovasi Penggunaan Aplikasi Naskah Dinas Elektronik (NADINE) di Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Sulawesi Selatan - Muthmainnah, Nurjayanti; Andi Cudai Nur; Muhammad Nur Yamin (Universitas Negeri Makassar, 2025)
This research aims to find out the Innovation of the use of Electronic Service Screenplay Application (NADINE) in the Regional Office of the Regional Directorate General of Treasury of South Sulawesi Province This research is qualitative, so as to achieve the research objectives used data collection techniques namely observation/observation, interview and documentation. This study uses four indicators: Having a Specialty, Having a Featured or Element of Update, Having a Planned Program, and Having a Goal. The results of this study showed that Innovation of the use of Electronic Service Screenplay Applications (NADINE) in the Regional Office of the Treasury Directorate General of South Sulawesi Province can be said to be “optimal” based on the theory indicator of Miles B, Matthew (1973) namely: 1) Has a peculiarity, lies in advanced security features, user access using Single Sign On (SSO), a barcode-shaped digital signature, as well as automatic notification systems that speed up administration processes. With monitoring capabilities that enable real-time tracking of document status, NADINE not only saves time but also improves efficiency in administrative management. 2) Having a feature or element of renewal, this innovation has replaced paper-based manual systems with more efficient and structured digital systems. This innovation not only accelerates workflow, but also improves integration and collaboration between users, as well as saves operational budgets. With advanced features such as status monitoring, service manuscript templates, barcode-shaped electronic signatures, disposition and follow-up management features, collaboration features with Microsoft O365, NADINE creates a more organized and responsive system to user needs. 3) Having a Planned Program, NADINE Application is designed and implemented according to well-planned programs, including needs analysis, integrated system development, structured training, and continuous evaluation. This innovation not only improves the efficiency of managing the manuscript of the service, but also demonstrates a commitment to the modernization of administration. 4) Having a Purpose, NADINE App was created with the aim of establishing integrated information databases, supporting e-government policies, and facilitating document search while reducing the risk of loss. NADINE also supports paperless culture that is in line with go green movement, improving administrative performance, and environmental preservation. This application is expected to perfect the Accuracy Governance system at the Regional Office of the Provincial Directorate General of South Sulawesi.